1994
DOI: 10.1203/00006450-199412000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Stress: Effects of Hypoglycemia and Hypoxia on Adrenal Tyrosine Hydroxylase Gene Expression

Abstract: Catecholamines (CA) are released from and resynthesized in the adrenal medulla in response to stress. In the mature animal, stimulus-secretion-synthesis coupling occurs through transsynaptic (neuronal) activity. In contrast, in the immature animal, before functional adrenal innervation, certain stressors (hypoglycemia and glycopenia) do not result in CA release. Additionally, it is not known whether release and biosynthesis remain coupled in the neonate as they are in the adult. Therefore, to evaluate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
4
12
1
Order By: Relevance
“…Consistent with all prior work (Ref. 16 and review in Ref. 24), our results confirmed that the maximal epinephrine response to hypoglycemia (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with all prior work (Ref. 16 and review in Ref. 24), our results confirmed that the maximal epinephrine response to hypoglycemia (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The intricate neuroendocrine communication between the HPA axis and the autonomic nervous system occurs at peripheral and central levels and is of relevance to clinical medicine (1,2,50,51). Patients with mutations in the TH gene (52,53) have recently been discovered, and there are many diseases associated with catecholamine depletion and͞or adrenomedullary impairment, including diabetes (54, 55), Addison's disease (56), 21-OH deficiency (7), and prenatal hypoxemia (57). Alteration in catecholamine pathways will therefore result in an increase in susceptibility to various stressors because of impaired function of both the autonomic nervous system and the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathoadrenal transmitter systems mature to adult capacity a week or more after birth in response to progressive cholinergic innervation, exposure to growth factors, and hormonal influences from both the hypothalamic-pituitary-adrenal cortical and thyroid hormonal systems (1)(2)(3)(4)(5)(6). Although the importance of these conventional control mechanisms is well established, the evolutionary significance of other exogenous stimuli can be considered in a broader view of environmentally derived signal-transduction.…”
mentioning
confidence: 99%